The Effects of Pre-Pregnancy Body Mass Index and Weight Gain During Pregnancy on Perinatal Outcomes: A Retrospective Cohort Study - Yurtcu, Engin; Mutlu, Sibel; Ozkaya, Enis (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVE: To investigate the effects of pre-pregnancy body mass index and weight gain during pregnancy on perinatal outcomes and delivery mode. STUDY DESIGN: In this retrospective cohort study, 722 pregnant women giving birth between 2018-2019 were screened from our hospital database. First, they were divided into four groups according to their pre-pregnancy body mass index (low-weight/normal-weight/overweight/obese), and then they were redivided into three groups according to pregnancy weight gain (≤7/8-15/≥16 kg). Prenatal body mass index and pregnancy weight gain were compared concerning maternal-neonatal results and mode of delivery. RESULTS: According to pre-pregnancy body mass index, among the obese pregnant group, gestational diabetes mellitus (p<0.001), preeclampsia (p=0.029), preterm delivery (p=0.011) and cesarean delivery (p=0.061) rates were more common. As the body mass index increases, neonatal intensive care requirement (p=0.0020) and low 1st minute APGAR scores (p=0.019) were detected more frequently. However, as pregnancy weight gain decreased, preterm delivery (p=0.041) increased. Also, birth weight increased (p<0.001) with the weight gain of the pregnant. Pregnant women gaining more than 16 kg were associated either with a lower <2500 g or a higher birth weight risk >4000 g. CONCLUSION: Pre-pregnancy high body mass index is associated with negative obstetric outcomes like gestational diabetes, preeclampsia, preterm delivery, and increased cesarean rates, and poor fetal incidences with a low APGAR score and high neonatal intensive care admission rates.